(untitled) (Veterinary Science, 2017)
When the fattening systems are evaluated in a given area it is a need of respite from the usual changes of the juncture of the business and support the physical variable analysis that explain the livestock production. In the present work, data from 1990 to 2011 was collected, which help to shown the trend of livestock production in the north-east of La Pampa, Argentina. From the analysis of the data, it can be seen the impact of the advancement of the agricultural activities in relation to the livestock production. There also was an underlying subject during the study period, the economic-financial component, which was of paramount matter throughout the analyzed years, but it will not be subject of study during the present work.